Measuring stress in podiatric students in Spain: psychometric validation and adaptation of the KEZKAK questionnaire - Ortega-Ávila, Ana Belén; Cervera-Garvi, Pablo; Jiménez-Cebrián, Ana María; Chicharro-Luna, Esther; García-Payá, Irene; Gijón-Noguerón, Gabriel (PeerJ Publishing, 2020)
Objective. The study aim was to develop a linguistic-cultural adaptation of theKEZKAK questionnaire to be completed during the practicum of podiatric medical students in Spain, to validate the questionnaire and to evaluate its psychometric properties. Methods. The cross-sectional study was carried out in two stages: 1. Cross-cultural adaptation; 2. Clinimetric validation based on assessments of interobserver reliability, test-retest reliability and internal consistency. The participants were podiatric medical students at the universities of Malaga and Miguel Hernandez, Alicante (Spain) and were recruited during the period February October 2019. The following inclusion criteria were applied: aged at least 18 years, studying the third or fourth year of a university degree in Podiatry. All gave signed informed consent and completed the State-Trait Anxiety Inventory and the Podiatry version of the KEZKAK questionnaire. No sampling was performed and thus the entire eligible population was included in the study. Results. The analysis was based on 205 participants (33.5% male, 66.5% female), with a mean age of 23.05 (SD 5.37) years. Internal consistency was excellent, with a Cronbach's alpha of 0.95. This version of the questionnaire had five factorial structures (61.18%). Nofloor/ceiling effect was observed in any item. TheKEZKAKpresented high test-retest reliability after 21 days, with an overall ICC of 0.95 (95% CI [0.93 0.98]). Conclusion. For university students of podiatry in Spain, the KEZKAK Podiatry version questionnaire is a valid, reliable instrument for measuring stressors during the practicum.
Keywords: Estudiantes - Aspectos psicológicos; podiatry; Reliability; Validity; kezkak